Right-Sizing Prenatal Care to Meet Patients' Needs and Improve Maternity Care Value. Issue 5 (May 2020) - Peahl, Alex F.; Gourevitch, Rebecca A.; Luo, Eva M.; Fryer, Kimberly E.; Moniz, Michelle H.; Dalton, Vanessa K.; Fendrick, A. Mark; Shah, Neel
Abstract : Prenatal care is one of the most widely used preventive care services in the United States, yet prenatal care delivery recommendations have remained largely unchanged since just before World War II. The current prenatal care model can be improved to better serve modern patients and the health care providers who care for them in three key ways: 1) focusing more on promotion of health and wellness as opposed to primarily focusing on medical complications, 2) flexibly incorporating patient preferences, and 3) individualizing care. As key policymakers and stakeholders grapple with higher maternity care costs and poorer outcomes, including lagging access, equity, and maternal and infant morbidity and mortality in the United States compared with other high-income countries, the opportunity to improve prenatal care has been given insufficient attention. In this manuscript, we present a new conceptual model for prenatal care that incorporates both patients' medical and social needs into four phenotypes, and use human-centered design methods to describe how better matching patient needs with prenatal services can increase the use of high-value services and decrease the use of low-value services. Finally, we address some of the key challenges to implementing right-sized prenatal care, including capturing outcomes through research and payment. Abstract : Tailoring prenatal care to meet patients' medical and support needs, rather than delivering care in a one-size-fits-all fashion, will improve care value and patient experience.